2020
DOI: 10.1177/1367006920938153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of language dominance on home reading practices of bilingual families

Abstract: Aims and objectives: Many children grow up in bilingual families; however, little is known about how these families use their two languages in their home reading practices. The goal of this study was to examine the effect of language proficiency on the shared storybook reading practices of bilingual families. Methodology: We gathered questionnaire data about home reading activities in French–English bilingual families with 5-year-old children ( n = 66) who had different proficiency levels in each language. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…While in our current study, we had an economically and educationally diverse group of parent respondents in both languages, we still observed effects of differing language statuses and the dominance of English within the wider community. Differences in language status collide with social factors like immigration and origin, and also the socio-cultural "status" of bilingualism or bilingual education for children, which can vary not only from country to country but region to region within a country (e.g., Gonzalez-Barrero et al, 2020). We see this reflected in the diverse (and sometimes contradictory) open-ended responses from our participants on questions of language mixing and language preferences during shared book reading.…”
Section: Considering the Multi-factor Influences On Dll Shared Book Readingmentioning
confidence: 91%
See 3 more Smart Citations
“…While in our current study, we had an economically and educationally diverse group of parent respondents in both languages, we still observed effects of differing language statuses and the dominance of English within the wider community. Differences in language status collide with social factors like immigration and origin, and also the socio-cultural "status" of bilingualism or bilingual education for children, which can vary not only from country to country but region to region within a country (e.g., Gonzalez-Barrero et al, 2020). We see this reflected in the diverse (and sometimes contradictory) open-ended responses from our participants on questions of language mixing and language preferences during shared book reading.…”
Section: Considering the Multi-factor Influences On Dll Shared Book Readingmentioning
confidence: 91%
“…In recent studies of language use in French/English bilingual families, Byers-Heinlein et al ( 2020) have emphasized the importance of considering the diversity of family characteristics and cultural values that have to be navigated even when "simply" trying to quantify a bilingual infant's relative exposure to each of their two languages. Within a similar French/English bilingual population, Gonzalez-Barrero et al (2020) found that language dominance in a household impacts a variety of reading choices and behaviors ranging from how many books families own in each language to how often parents translate or switch from one language to another while reading aloud with their young children, and that the less balanced in dominance the two languages are within a household the more of an impact the dominant language has on shared reading practices. Thus, understanding what influences language dominance in different families and communities will help us better understand home literacy practices for different kinds of dual-language learners.…”
Section: Considering the Multi-factor Influences On Dll Shared Book Readingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some research suggests that families may tend to emphasize one language over the other in their home literacy practices, leading to unbalanced exposure to each of the child's languages (Gonzalez-Barrero et al, 2021), and parents often lack access to literacy materials in heritage languages and bilingual formats (Ahooja et al, in prep. ).…”
Section: Bilingual Language Experience From Caregiversmentioning
confidence: 99%